MGMT Inhibition Suppresses Survivin Expression in Pancreatic Cancer. Issue 4 (May 2015) - Bobustuc, George C.; Patel, Anand; Thompson, Michael; Srivenugopal, Kalkunte S.; Frick, Jacob; Weese, James; Konduri, Santhi D.
Abstract : Objectives: Survivin, an antiapoptotic gene inhibited by p53, is overexpressed in human cancers and correlates with chemotherapy resistance. Here, we investigated the mutual regulatory mechanism between MGMT (O 6 - methylguanine DNA methyltransferase) and survivin. Methods: This study used standard techniques for protein and messenger RNA levels, promoter activity, protein-DNA interaction, cell viability, and correlative animal model. Results: O 6 -benzylguanine (BG), a potent inhibitor of MGMT (a DNA repair protein), curtails the expression of survivin in pancreatic cancer. Silencing MGMT by small interfering RNA down-regulates survivin transcription. p53 inhibition enhances MGMT and survivin expressions. When p53 was silenced, BG-induced MGMT inhibition was not associated with the down-regulation of survivin, underscoring the regulatory role of p53 in the MGMT-survivin axis. O 6 -benzylguanine inhibits survivin and PCNA (proliferating cell nuclear antigen) at messenger RNA and protein levels in PANC-1 and L3.6pl cells and decreases survivin promoter activity via increased p53 recruitment to the survivin promoter. In orthotopic pancreatic xenografts established in nude mice, BG ± gemcitabine (GEM) decrease survivin expression in tumor tissue; protein levels and immunohistochemistry show significant decrease in survivin and PCNA levels, which correlate with increased sensitivity to GEM. Conclusions: MGMT inhibition is associated with decrease in survivin expression and increase in sensitivity to GEM in pancreatic cancer.